2017
DOI: 10.1096/fj.201700316r
|View full text |Cite|
|
Sign up to set email alerts
|

Matrine prevents bone loss in ovariectomized mice by inhibiting RANKL‐induced osteoclastogenesis

Abstract: Osteoporosis is a metabolic bone disease characterized by decreased bone density and strength due to excessive loss of bone protein and mineral content. The imbalance between osteogenesis by osteoblasts and osteoclastogenesis by osteoclasts contributes to the pathogenesis of postmenopausal osteoporosis. Estrogen withdrawal leads to increased levels of proinflammatory cytokines. Overactivated osteoclasts by inflammation play a vital role in the imbalance. Matrine is an alkaloid found in plants from the Sophora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 50 publications
2
75
0
Order By: Relevance
“…Activation of the MAPK and the AKT pathway play significantly in osteoclast formation (Chen et al, ; Deepak, Kasonga, Kruger, & Coetzee, ). Therefore, to determine the effects of THF on MAPK and AKT following the stimulation of RANKL in RAW 264.7 and BMM cells, we investigated the phosphorylation of ERK, JNK, p38, and AKT by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the MAPK and the AKT pathway play significantly in osteoclast formation (Chen et al, ; Deepak, Kasonga, Kruger, & Coetzee, ). Therefore, to determine the effects of THF on MAPK and AKT following the stimulation of RANKL in RAW 264.7 and BMM cells, we investigated the phosphorylation of ERK, JNK, p38, and AKT by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…RANKL‐induced NF‐kB activation is known to be essential for osteoclast differentiation and function (Chen et al, ). NF‐κB was activated by RANKL through phosphorylation of IKK and subsequent phosphorylated and degradation of IκBα (Deepak et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear factor of activated T-cell cytoplasmic 1 (NFATc1) is the central transcriptional factor in osteoclastogenesis and is responsible for the transcription of osteoclast-related genes, including matrix metalloproteinase (MMP)-9, cathepsin K, latent transforming growth factor beta binding protein 3, tartrate-resistant acid phosphatase (TRAP), and c-Src [4]. Finally, intracellular Ca 2+ is released, and NFATc1 is activated and osteoclastogenesis is promoted [5]. Previous studies demonstrated that overactive osteoclast function could also be induced by a deficiency of estrogen accompanied by increased levels of proinflammatory cytokines and RANKL after menopause [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the involvement of EPCs in the early bone resorption activity is an important event for promoting skeletal development [8, 14]. OCs are specialized multinucleated cells derived from hematopoietic stem cells or monocytes/macrophage progenitor cells [15]. There are three different stages during osteoclastogenesis: preosteoclast (Pre-OC), newborn osteoclast (N-OC) and mature osteoclast (M-OC) [16-18].…”
Section: Introductionmentioning
confidence: 99%